TIME COORDINATION OF SELECTED PUBLIC TRANSPORT LINES IN PROSTĚJOV (Perner's Contacts, 2011)
The paper deals with modelling of the synchronization of departures from the transfer stations using Max-plus algebra in Scilab. The problem of passengers’ transfer is formulated using mathematical Max-plus algebra. In the next part of the paper there is a characteristic of Prostějov public transport and an introduction to Max-plus algebra operations that are used for modelling of the synchronization of public transport lines in Prostějov.
Keywords: Synchronization; interchange stops; modelling; Max-plus algebra; Scilab